Sodium Bicarbonate for Control of ICP: A Systematic Review. Issue 1 (January 2018) - Zeiler, Frederick A.; Sader, Nicholas; West, Michael; Gillman, Lawrence M.
Abstract : Objective: Our goal was to perform a systematic review of the literature on the use of intravenous sodium bicarbonate for intracranial pressure (ICP) reduction in patients with neurologic illness. Methods: Data sources: articles from MEDLINE, BIOSIS, EMBASE, Global Health, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to April 2015), reference lists of relevant articles, and gray literature were searched. Data extraction: 2 reviewers independently extracted data including population characteristics and treatment characteristics. The strength of evidence was adjudicated using both the Oxford and Grading of Recommendation Assessment Development and Education methodology. Results: Our search strategy produced a total 559 citations. Three original articles were included in the review. There were 2 prospective studies, 1 randomized control trial and 1 single arm, and 1 retrospective case report. Across all studies there were a total of 19 patients studied, with 31 episodes of elevated ICP being treated. Twenty-one of those episodes were treated with sodium bicarbonate infusion, with the remaining 10 treated with hypertonic saline in a control model. All elevated ICP episodes treated with sodium bicarbonate solution demonstrated a significant drop in ICP, without an elevation of serum partial pressure of carbon dioxide. No significant complications were described. Conclusions: There currently exists Oxford level 4, Grading of Recommendation Assessment Development and Education D evidence to support an ICP reduction effect with intravenous sodium bicarbonate in TBI. No comments on its impact in other neuropathologic states, or on patient outcomes, can be made at this time. Abstract : Supplemental Digital Content is available in the text.